The New Working Alliance Inventory-Short Form for Multicultural Counselor’s Candidates in Indonesian Culture - Herdi, Herdi; Kartadinata, Sunaryo; Taufiq, Agus (International Conference on Elementary Education, 2020)
The 36-item of Working Alliance Inventory-Therapist (WAI-T) is useful assessment tool, given its rigorous development and good psychometric properties. However, the measures length can prohibit use. This study aim is to adapt, develop, and exam psychometric properties of the New WAI-T-Short Form (New WAI-T-SF) for multicultural counselor’s candidates in Indonesian culture. This study used instrument adaptation procedures. In this study, we used a sample of 517 sixth semester of counselor’s candidates from 11 Department of Guidance and Counseling in Indonesia. Operationally, data analysis was performed by using Rasch Model version 3.75. The results showed that the New WAI-T-SF had satisfying psychometric properties, i.e. item measure, item fit order, DIF, person measure, person fit order, item-person maps, rating scale, test reliability, person reliability, and item reliability. Results suggest that the New WAI-T-SF can provide efficient and valid assessments of working alliance in Indonesian culture